The Tradiciones peruanas viewed from the civil engineering point of view - Ferrari Lavalle, Vanessa Lisbeth (2019)
This essay will analyze the traditions «El puente de los pecadores» and «Los azulejos de San Francisco», as they reveal the situation of the civil engineering specialty at the time when they were written, based on the constructions mentioned in each one.